Pattern of thyroid disorders in ENT OPD of Nobel Medical College in Eastern Nepal - Thakur, Sanjeev Kumar; Agrawal, Manish; Ghimire, Nisha; Bedajit, R.K.; Roy, Pratap (Journal of Diabetes and Endocrinology Association of Nepal, 2019)
Background: Thyroid dysfunction is a major health problem in eastern Nepal with a high prevalence and the pattern of thyroid disorders. Previous studies have shown the tendency of hypothyroidism to increase with the age and being more common in women. Objective: this study was undertaken to study the various possible manifestations of thyroid disorders and their relation to age in female population in eastern Nepal. Methods: This was a hospital based study, conducted in the Department of ENT of Nobel Medical College and teaching hospital in eastern Nepal. A total of 153 female subjects, who attended the outpatients department (OPD) for thyroid screening were enrolled in the study. Blood samples were collected and thyroid assay was done (fT3, fT4, and TSH). Data was tabulated and analysed. Results: On analyzing the Thyroid profile of 153 subjects, 107 (69.93%) of them were found to be of euthyroid status. Rest of them had abnormal status. Subclinical hypothyroidism status was found in 31 (20.26%) subjects, while frank hypothyroidism was found in 9 (5.88%) cases. Subclinical hyperthyroidism and frank hyperthyroidism was found in 3 (1.96%) cases each. The fT3 level was of high normal level in the less than 40 years age group, while it was low normal in the above 40 years age group. On analysis, with ANOVA, there was significant difference in fT3 values among three age groups. But, no significant difference was found for fT4 level among age groups. The TSH level was shown to differ significantly among three different age groups. The normal range of TSH increased with increasing age. On analyzing the correlation of Thyroid function parameters, fT3 and fT4 values did not correlate with age, but, TSH was positively correlated with age. This signifies that TSH increases with increasing age, which is also similar to the ANOVA results. Conclusion: the prevalence of thyroid disorder in the studied sample of eastern Nepal is found to be 30.07% and hypothyroidism was the commonest disorder in this study. There is a tendency of fT3 to decrease and TSH to increase with increasing age. However no definite pattern was found for fT4.